التكلفة على أساس النشاط ودورها في تحديد تكلفة الخدمة التعليمية لطالب التعليم الثانوي بولاية الخرطوم - الحسين، خديجة مصطفى عبدالرحمن; النجيب، إسماعيل عثمان محمد (جامعة السودان للعلوم والتكنولوجيا, 2020)
تناولت الدراسة التكلفة على أساس النشاط ودورها في تحديد تكلفة الخدمة التعليمية لطالب التعليم الثانوي بولاية الخرطوم، حيث تمثلت مشكلة الدراسة في دور التكلفة على أساس النشاط في تحديد تكلفة الخدمة التعليمية لطالب التعليم الثانوي، هدفت الدراسة إلى كيفية تحديد تكلفة الخدمة التعليمية لطالب التعليم الثانوي من خلال تطبيق نظام التكلفة على أساس النشاط. استخدمت الدراسة المنهج الوصفي التحليلي لاختبار العينات والبالغ عددها (189) استبانة وجهت إلى مديري وأساتذة المدارس الثانوية بنسبة استرداد بلغت 91.53%، من أهم نتائج الدراسة أن تطبيق التكلفة على أساس النشاط يعمل على تحديد الأنشطة الأكثر ارتباطا بالخدمة التعليمية مما يسهل من تحديد تكلفة الخدمة التعليمية للطالب بصورة عادلة، التكلفة على أساس النشاط توفر معلومات تساعد في تقويم القرارات الإدارية لتحسين التخطيط بمؤسسات التعليم بالمرحلة الثانوية، تطبيق التكلفة على أساس النشاط يساعد في فهم أفضل الطرق التي يتم بها توليد الأرباح ويحقق مزايا تنافسية لمؤسسات التعليم الثانوي بالصورة المطلوبة. أوصت الدراسة بضرورة تطبيق التكلفة على أساس النشاط للعمل على التخلص من الأنشطة التي لا تضيف قيمة مما يؤدي إلى تخفيض التكلفة وتقديم الخدمة لطالب المرحلة الثانوية بصورة أفضل.
The study examined Cost Based Activity (ABC) and its role in determining student learning cost service at secondary educational level in Khartoum State. The problem of study was to identify the role of ABC in determining the cost of learning service for the student at secondary educational level. The study aimed to find out how to determine the cost of learning service for the student at secondary educational level through applying the ABC system. The analytical descriptive method was used to select the samples that amounted to (189) questionnaires addressed to the principals and teachers of secondary schools level, achieving a response rate of %91.53. The most significant findings showed that the application of ABC would identify the most related activities to learning service which facilitate fairly the determining of the learning service cost, the cost based on the activity provides information that helps in evaluating administrative decisions to improve planning in educational institutions at the secondary level, and applying cost- based activity helps in understanding the best ways in which profits are generated and achieves competitive advantages for secondary education institutions as required. The study recommended that ABC should be applied to get rid of unnecessary activities, which did not add any value, thus leading to cost reduction, and providing suitable service to the student at secondary level.
Keywords: التعليم الثانوي -- الخدمات التعليمية -- التكلفة المالية -- السودان